NILAI-NILAI KEISLAMAN DALAM RUMAH TINGGAL (Studi Kasus: Kampung Kauman Kudus, Kampung Kauman Solo dan Perumahan Muslim Darussalam 3 Sleman-DIY) - , IR. WIDYASTUTI NURJAYANTI, MT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
\"Islamic values in the residence\" is a study about Islamic values in the residence which is based on Islamic principles appropriate guidance of the Qur'an and Hadith. The case studies in this research is Kauman Kudus, Kauman Solo and Muslim Housing Darussalam 3, Sleman, Yogyakarta. This issue of the research are public demand and the weakening of Islamic residential character of Muslim life. This study is an operational basis of Islamic values in residences obtained from the literature and combined assessment between the theory of Rapoport, Ronald, Hakim, Mortada, and sustainable architecture. This study used the postpositivistik paradigm, as well as methods and strategies of case studies with multiple case. The purpose of this study is: a) explore and search for the presence of Islamic values in the form of Islamic activity in residences and spatial manifestation in residences in Kauman , Kauman Solo and Muslim Housing Darussalam 3 Sleman DIY